2021
DOI: 10.1111/ppc.12997
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and its relationship with suicide probability and Self‐Esteem: A case study in a university in Turkey

Abstract: Purpose The aim of this study is to investigate to what extent childhood trauma affects suicide probability and self‐esteem of university students. Design and Methods In this descriptive study, 3602 university students continuing their education in the 2019–2020 academic year were selected into the sample. The data in the study were collected using a personal information form, “Childhood Trauma Questionnaire (CTQ)”, “Suicide Probability Scale (SPS)” and Rosenberg Self‐Esteem Scale (RSES). The data were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…Our results are consistent with past research showing that university students with traumatic experiences have lower total SES scores [11,58]. In addition, as a state of being self-satisfied without considering oneself inferior or superior, a decline in SE may induce mental health problems [58]. A meta-analysis of longitudinal studies covering 77 studies on depression and 18 on anxiety symptoms confirmed the negative effect of SE on depression and anxiety symptoms levels [59].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with past research showing that university students with traumatic experiences have lower total SES scores [11,58]. In addition, as a state of being self-satisfied without considering oneself inferior or superior, a decline in SE may induce mental health problems [58]. A meta-analysis of longitudinal studies covering 77 studies on depression and 18 on anxiety symptoms confirmed the negative effect of SE on depression and anxiety symptoms levels [59].…”
Section: Discussionsupporting
confidence: 92%
“…In other words, abused children are less likely to perceive themselves as valuable and important and have less ability to deal with emotional problems compared to those who do not experience abuse [56,57]. Our results are consistent with past research showing that university students with traumatic experiences have lower total SES scores [11,58]. In addition, as a state of being self-satisfied without considering oneself inferior or superior, a decline in SE may induce mental health problems [58].…”
Section: Discussionsupporting
confidence: 89%